ChemInform Abstract: Synthesis of Bis‐spiropyrans Based on 6, 8‐Diformyl‐5, 7‐dihydroxy‐4‐methylcoumarin and Photochromic Properties Thereof. Issue 40 (October 2015) - Nikolaeva, Olga G.; Karlutova, Olga Yu.; Cheprasov, Alexander S.; Metelitsa, Anatoly V.; Dorogan, Igor V.; Dubonosov, Alexander D.; Bren', Vladimir A.
Abstract The reaction of coumarin derivative (I) with indolium perchlorates of type (II) or (IV) yields bis‐spiropyrans of type (III) or the corresponding merocyanine forms of type (V).